2020
DOI: 10.1093/glycob/cwz105
|View full text |Cite
|
Sign up to set email alerts
|

Application of a gut-immune co-culture system for the study of N-glycan-dependent host–pathogen interactions of Campylobacter jejuni

Abstract: An in vitro gut-immune co-culture model with apical and basal accessibility, designed to more closely resemble a human intestinal microenvironment, was employed to study the role of the N-linked protein glycosylation pathway in Campylobacter jejuni pathogenicity. The gut-immune co-culture (GIC) was developed to model important aspects of the human small intestine by the inclusion of mucin-producing goblet cells, human enterocytes and dendritic cells, bringing together a mucus-containing epithelial monolayer wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 46 publications
2
17
0
Order By: Relevance
“…Packaging of PglB into OMVs may enable glycosylation of sites not typically found in the membrane; however despite this, we and others have observed no such cytoplasmic N-glycosites, even at low levels, which may imply that PglB does not occur in OMVs, or that OMVs are not induced (or collected) under the culture conditions employed in the N-glycosite discovery studies conducted thus far. C. jejuni OMV composition is however, altered in pgl-negative compared with wild-type C. jejuni, 113 suggesting N-glycosylation does impact protein packaging, although no differences were observed in the ability of OMVs from either pgl positive or negative bacteria to induce an immune response. 113 Putative functions of C. jejuni protein N-glycosylation Deletion of genes from the pgl cluster (except pglI) results in C. jejuni that are poorly able to colonize chickens and display reduced adherence to, and invasion of, human epithelial cells.…”
Section: Identification Of Proteins Modified By N-glycosylation In C Jejunimentioning
confidence: 95%
See 2 more Smart Citations
“…Packaging of PglB into OMVs may enable glycosylation of sites not typically found in the membrane; however despite this, we and others have observed no such cytoplasmic N-glycosites, even at low levels, which may imply that PglB does not occur in OMVs, or that OMVs are not induced (or collected) under the culture conditions employed in the N-glycosite discovery studies conducted thus far. C. jejuni OMV composition is however, altered in pgl-negative compared with wild-type C. jejuni, 113 suggesting N-glycosylation does impact protein packaging, although no differences were observed in the ability of OMVs from either pgl positive or negative bacteria to induce an immune response. 113 Putative functions of C. jejuni protein N-glycosylation Deletion of genes from the pgl cluster (except pglI) results in C. jejuni that are poorly able to colonize chickens and display reduced adherence to, and invasion of, human epithelial cells.…”
Section: Identification Of Proteins Modified By N-glycosylation In C Jejunimentioning
confidence: 95%
“…C. jejuni OMV composition is however, altered in pgl-negative compared with wild-type C. jejuni, 113 suggesting N-glycosylation does impact protein packaging, although no differences were observed in the ability of OMVs from either pgl positive or negative bacteria to induce an immune response. 113 Putative functions of C. jejuni protein N-glycosylation Deletion of genes from the pgl cluster (except pglI) results in C. jejuni that are poorly able to colonize chickens and display reduced adherence to, and invasion of, human epithelial cells. 114,115 Additional recent modelling of C. jejuni virulence in a human small intestine-like gut-immune co-culture model also revealed that pgl-negative C. jejuni (in this case, pglE deletion) were vastly deficient (B100 times less) in adherence and invasion.…”
Section: Identification Of Proteins Modified By N-glycosylation In C Jejunimentioning
confidence: 95%
See 1 more Smart Citation
“…Interestingly, duodenal, ileal and colonic organoid cultures derived from different donors demonstrate a differential response to infection and differing patterns of bacterial adhesion, possibly due to the genetic variability based on the tissue of origin ( 89 ). A co-culture model developed to study the host-pathogen interactions of C. jejuni incorporates intestinal enterocytes, mucin-secreting goblet cells and dendritic cells, thus combining a mucus-secreting epithelial layer with cellular elements of the intestinal innate immune system ( 92 ).…”
Section: Translational Application Of Organoid Models In Ibdmentioning
confidence: 99%
“…To date, the majority of reported long-term (up to 2 weeks) co-cultures with live bacteria in contact with epithelial cells have been in microfluidic devices 12 , 13 , although primarily short-term (< 4 h) co-cultures have been reported in static systems 14 18 , with some recent medium-term (24 h) exceptions 19 . Notably, reports of static cultures incorporating immune components, specifically dendritic cells 15 , 19 or macrophage simulating differentiated THP-1 cells 20 , and bacteria result in high accumulation of dead epithelial cells and significant increases in paracellular permeability when compared to control cultures, even when cultured with bacteria for as little as 2 h. This suggests that flow is an important factor in preserving epithelial health and barrier function. It has been proposed that flow is important for preventing the accumulation of microbial waste and microbial overgrowth, thus aiding in establishing a steady-state microenvironment 12 .…”
Section: Introductionmentioning
confidence: 99%